Evaluating the Effectiveness of Trade Conditions in Fund-Supported Programs. (Policy Papers; Policy Paper ;, 2005)
Approximately half of the countries that had IMF-supported programs during 1993-2003 also had trade-related conditions. A large literature has shown that trade openness is an essential part of the environment in which economic growth and poverty reduction take place.